2018
DOI: 10.3390/cryst8040158
|View full text |Cite
|
Sign up to set email alerts
|

(BEDT-TTF)2Cu2(CN)3 Spin Liquid: Beyond the Average Structure

Abstract: We present here the first accurate determination of the exact structure of κ-(BEDT-TTF) 2 Cu 2 (CN) 3 . Not only did we show that the room temperature structure used over the last twenty years was incorrect, but we were also able to correctly and precisely determine it. The results of our work provide evidence that the structure presents a triclinic symmetry with two non-equivalent dimers in the unit cell, which implies a charge disproportionation between the dimers. However, structural refinement shows that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 66 publications
2
19
1
Order By: Relevance
“…In closing, we note that the dielectric response scenario presented in this section, was recently backed up by the theoretical approach developed to explain anomalous dielectric response in strongly correlated molecular solids [62]. Most importantly, in-depth X-ray diffraction measurements of κ-CuCN in the wide temperature range and refinements, complemented by DFT calculations, have demonstrated that two nonequivalent dimers exist in the unit cell due to the reduced symmetry of the whole crystal [63].…”
Section: Quantum Spin Liquids In Disordered κ-(Bedt-ttf) 2 Cu 2 (Cn) mentioning
confidence: 78%
“…In closing, we note that the dielectric response scenario presented in this section, was recently backed up by the theoretical approach developed to explain anomalous dielectric response in strongly correlated molecular solids [62]. Most importantly, in-depth X-ray diffraction measurements of κ-CuCN in the wide temperature range and refinements, complemented by DFT calculations, have demonstrated that two nonequivalent dimers exist in the unit cell due to the reduced symmetry of the whole crystal [63].…”
Section: Quantum Spin Liquids In Disordered κ-(Bedt-ttf) 2 Cu 2 (Cn) mentioning
confidence: 78%
“…The space group is commonly solved in monoclinic P2 1 /c, in which all four BEDT-TTF molecules are equivalent [69,70]. However, the P2 1 /c is only the average structure, while the exact structure presents a triclinic symmetry with two non-equivalent crystallographic sites [71,72]. In the panel (d) to (f) the projection of one of the layers is shown.…”
Section: β -(Bedt-ttf) 2 Sf 5 Rsomentioning
confidence: 99%
“…The situation is more complex when disorder also occurs in the anion lattice, as for instance in κ-(BEDT-TTF) 2 Cu 2 (CN) 3 . [185,[187][188][189] adding an extra structural degree of freedom.…”
Section: Shown Inmentioning
confidence: 99%